AGRIBISNIS KOPI DALAM MENDUKUNG PENGEMBANGAN AGROWISATA DI DESA COLOL, KECAMATAN LAMBA LEDA TIMUR, KABUPATEN MANGGARAI TIMUR (Coffee Agribusiness In Supporting Agrotourism Development In Colol Village, Lamba Leda Timur District, East Manggarai District) - MIA, MARIA MAGDALENA; ASNAH, ASNAH; DYNASARI, DYNASARI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2024)
Colol Village is a wilaya located in East Manggarai Regency, East Nusa Tenggara Province, which has good environmental and geographical characteristics, fertile soil and a suitable climate for coffee cultivation. The coffee varieties that are being developed are Arabica coffee and Robusta coffee. The people of East Manggarai have a cultural tradition that is close to coffee. The aim of this research is to analyze the factors that influence coffee production in Colol Village, determine farmers' perceptions of agrotourism development in Colol Village and describe the implementation of the coffee agribusiness system in Colol Village, East Manggarai Regency. This research used mixed methods with a sample size of 56 people using multiple linear regression data analysis methods, Likert scale analysis and descriptive qualitative analysis. The results of the research show that in coffee production the factors of land area, farming experience, farmer age, education level, household income, and coffee sales income level influence the development of agrotourism in Colol Village, East Manggarai Regency and based on Likert scale analysis, Colol coffee farmers agree with the development of coffee agrotourism in Colol Village and coffee production and agrotourism potential are related, the potential for coffee farming as a tourist attraction thereby strengthening the local economy and creating sustainable opportunities for the development of Colol village, East Manggarai